Biological and social factors that influence women's health during climacteric and menopause - Eneida Bravo Polanco; Narciso Águila Rodríguez; Carmen Amalia Benítez Cabrera; Dayamí Rodríguez Soto; Alexander José Delgado Guerra; Alina Centeno Díaz (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2019)
Menopause is a period in a woman's life subject to many changes. It is known that it is the complete cessation of menstruation, but the symptoms produced by it are often underestimated, even by health personnel. Through time, it has been mentioned in history, literature, culture, etc. There are many factors which condition the climacteric and menopause. The objective of this review is to compile information on the biological and social aspects that influence women´s health at this stage of their lives.